State-of-the-art review on research and application of original bamboo-based composite components in structural engineering. (January 2022) - Chen, Zhihua; Ma, Rui; Du, Yansheng; Wang, Xiaodun
Abstract: Pursuing ecological construction methods, such as green building materials and environmentally construction techniques, is an essential way of sustainable development. Bamboo, one kind of fast growing and high yielding renewable natural resource, has gradually attracted civil engineers' attention to be a promising building element in civil engineering. Original bamboo-based composites made by original bamboo and other conventional materials also have great potential to be utilized in structure construction. Through the combination process the advantages of different materials could be taken while the disadvantages could be reduced. This paper firstly gave the definition of original bamboo-based composite material (BCM) and composite component (BCC), and then outlined the recent patterns and trends in the field of BCCs, including columns, beams, slabs and walls. The researches of connections between the bamboo and the other materials were concluded and compared. The analysis and design methods of BCCs were summarized afterwards. Some issues and challenges about bamboo utilization in structural field were discussed. The perspective and conclusions of this paper may provide some enlightenment of future work to the further research and use of bamboo.